Evaluación de impacto ambiental del sector eléctrico en el norte de México: evolución histórica e implicaciones para la sostenibilidad - María E. González Ávila (El Colegio Mexiquense, A.C., 2006)
We revised and analysed the development and content of the Reportes de Evaluación de Impacto Ambiental REIA (Evaluation Reports on Environmental Impact) for electricity projects in the last 30 years in Northern Mexico. We also collected and analysed information about the population and the economical situation in the region. We found that neither the process nor the format of the REIA have evolved. The main limitations are: lack of knowledge, ambiguity in the methodological aspects and specific environmental regulations. We recommend the development of REIA specific to the electrical sector, in order to include not only the environmental part but also the public participation and the specific economical aspects of the Northern Mexican region.